Preparation method of positive electrode material compositely coated and modified by solid electrolyte and solid-state battery
Through oxide-polymer composite cladding technology, the problem of increasing interface resistance between traditional positive electrode materials and solid electrolytes is solved, and the rapid transmission of lithium ions and improvement of battery performance is achieved, which significantly extends the battery's cycle life and improves safety performance.
Patent Information
- Application Number
- CN202411718753.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
AI Technical Summary
When traditional positive electrode materials come into contact with high rigid solid electrolyte, they can easily lead to problems such as increasing interface resistance, impeded ion transmission, and degradation of battery circulation performance.
The oxide-polymer composite cladding technology is used to uniformly disperse oxides and polymers through the sol-gel method to form a dense composite cladding layer, and optimize the ionic conductivity, mechanical strength and electrochemical stability of the cladding layer.
It effectively reduces the interface resistance between the positive electrode and the solid electrolyte, promotes the rapid transmission of lithium ions, improves the charging and discharging efficiency and energy density of the battery, extends the cycle life of the battery, and enhances the safety performance of the battery.
Smart Images

Figure CN119627067A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a method for preparing a positive electrode material modified by a solid-state electrolyte composite coating and a solid-state battery. Background Art
[0002] A solid-state battery is a battery that uses solid electrodes and solid electrolytes. The negative electrode material of a solid-state battery can be a composite negative electrode of nano-silicon and graphite, and the positive electrode can be lithium manganese oxide, a lithium-rich manganese-based material, or a lithium-free positive electrode material. The electrolyte is a solid electrolyte with an energy density of 300 to 450 watt-hours per kilogram. Solid-state batteries use solid electrolytes to replace the electrolytes and diaphragms of traditional lithium-ion batteries. They are safer, have higher energy density, and have stronger cycle performance. They have become the main research and development direction of the next generation of power batteries. Solid electrolytes can be roughly divided into three categories: inorganic electrolytes, solid polymer electrolytes, and composite electrolytes. Since the power-to-weight ratio of solid-state batteries is relatively high, they are ideal batteries for electric vehicles.
[0003] As the next generation of energy storage devices with high energy density, long life and high safety, the commercialization process of solid-state batteries is constrained by key issues such as the interface compatibility between solid electrolytes and electrode materials, ion conduction efficiency, and mechanical stability. Traditional positive electrode materials are in direct contact with high-rigidity solid electrolytes, which can easily lead to problems such as increased interface resistance, obstructed ion transmission, and decreased battery cycle performance. Therefore, developing a modification technology that can effectively improve the interface properties between the positive electrode and the solid electrolyte has become a hot spot and difficulty in current solid-state battery research. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing a positive electrode material with a solid electrolyte composite coating modification and a solid-state battery, which solves the problems mentioned in the above background technology.
[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: a method for preparing a positive electrode material modified by a solid electrolyte composite coating, specifically comprising the following steps:
[0006] S1. Preparation of composite coating layer of positive electrode material:
[0007] (1) Selecting a suitable oxide solid electrolyte material and uniformly dispersing it in an organic solvent by a sol-gel method to form a stable oxide solution;
[0008] (2) Selecting a polymer solid electrolyte with high ionic conductivity and good flexibility, and dissolving it in an organic solvent with good compatibility to form a polymer solution;
[0009] (3) dispersing the positive electrode active material in the mixture of the above oxide and the polymer solution, and ensuring uniform coating by stirring, ultrasound or ball milling;
[0010] (4) vacuum drying the coated material at 80-150° C. or heat treating it in an inert atmosphere to remove excess solvent and form a dense oxide-polymer composite coating layer;
[0011] S2. Optimization of composite coating properties: By adjusting the ratio of oxide to polymer, the thickness of the coating, and the heat treatment conditions, the ion conductivity, mechanical strength, and electrochemical stability of the composite coating are optimized. The performance of the composite coating can also be further improved by adding a small amount of inorganic nanoparticles.
[0012] S3. Assembly of solid-state battery: using the modified positive electrode material, solid electrolyte, negative electrode material and separator, assembling into a battery according to conventional solid-state battery manufacturing process;
[0013] S4. Performance testing: Conduct electrochemical performance tests on the prepared solid-state batteries, including charge and discharge cycle stability, rate performance, energy density, coulombic efficiency, self-discharge rate and safety performance tests, to verify the improvement effect of the composite coating on battery performance.
[0014] Preferably, the usage ratio of the oxide solid electrolyte, the polymer solid electrolyte, the organic solvent and the positive electrode active material is 0.005-0.02 g: 0.005-0.02 g: 5-10 mL: 1 g.
[0015] Preferably, the oxide solid electrolyte includes at least one of aluminum oxide, zirconium oxide, and silicon oxide, and the polymer solid electrolyte includes at least one of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), and polyacrylonitrile (PAN).
[0016] Preferably, the positive electrode active material is LiNiCoMnO 2 or LiNi o.8 Co o.1 Mo o.1 O 2 The organic solvent includes at least one of ethanol, acetonitrile, N-methylformamide, and tetrahydrofuran, and the thickness of the oxide and polymer solid electrolyte coating layer is 1 to 5 nm.
[0017] Preferably, in S2, the inorganic nanoparticles are selected from titanium dioxide or carbon nanotubes.
[0018] Preferably, in S3, the solid electrolyte is selected from one of a sulfide solid electrolyte, an oxide solid electrolyte or a polymer solid electrolyte, and the negative electrode material is selected from one of lithium metal, lithium alloy or a silicon-based negative electrode.
[0019] A solid-state battery comprises a battery positive electrode material prepared by the above-mentioned preparation method, a solid electrolyte, a conductive agent and a binder.
[0020] Beneficial Effects
[0021] The present invention provides a method for preparing a positive electrode material modified by a solid electrolyte composite coating and a solid-state battery. Compared with the prior art, the present invention has the following beneficial effects: the method for preparing a positive electrode material modified by a solid electrolyte composite coating and a solid-state battery specifically include the following steps: S1, preparation of a composite coating layer of a positive electrode material; S2, optimization of the properties of the composite coating layer; S3, assembly of a solid-state battery; S4, performance testing; the oxide-polymer composite coating layer effectively reduces the interface resistance between the positive electrode and the solid-state electrolyte, promotes the rapid transmission of lithium ions, and improves the charging and discharging efficiency and energy density of the battery. The flexibility of the polymer is combined with the high mechanical strength of the oxide to improve the structural stability of the battery during the charging and discharging process, reduce the pulverization and peeling of the positive electrode material, and significantly prolong the cycle life of the solid-state battery by optimizing the composition and structure of the coating layer, reduce the capacity attenuation, and improve the cycle stability and reliability of the battery. The use of the solid electrolyte fundamentally avoids the safety problems that may be caused by the liquid electrolyte, such as leakage, combustion, explosion, etc. At the same time, the composite coating layer further enhances the thermal stability and chemical stability of the battery and improves the safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] See also Figure 1 The present invention provides three technical solutions: a method for preparing a positive electrode material modified by a solid electrolyte composite coating, specifically including the following embodiments:
[0025] Embodiment 1
[0026] S1. Preparation of composite coating layer of positive electrode material:
[0027] (1) selecting 0.0125 g of a suitable oxide solid electrolyte material and uniformly dispersing it in an organic solvent by a sol-gel method to form a stable oxide solution;
[0028] (2) selecting 0.0125 g of a polymer solid electrolyte having high ionic conductivity and good flexibility, and dissolving it in 7 mL of an organic solvent having good compatibility to form a polymer solution;
[0029] (3) dispersing 1 g of the positive electrode active material in the mixture of the above oxide and polymer solution, and ensuring uniform coating by stirring, ultrasound or ball milling;
[0030] (4) vacuum drying the coated material at 115° C. or heat treating it in an inert atmosphere to remove excess solvent and form a dense oxide-polymer composite coating layer;
[0031] S2. Optimization of composite coating properties: By adjusting the ratio of oxide to polymer, the thickness of the coating, and the heat treatment conditions, the ion conductivity, mechanical strength, and electrochemical stability of the composite coating are optimized. The performance of the composite coating can also be further improved by adding a small amount of inorganic nanoparticles.
[0032] S3. Assembly of solid-state battery: using the modified positive electrode material, solid electrolyte, negative electrode material and separator, assembling into a battery according to conventional solid-state battery manufacturing process;
[0033] S4. Performance testing: Conduct electrochemical performance tests on the prepared solid-state batteries, including charge and discharge cycle stability, rate performance, energy density, coulombic efficiency, self-discharge rate and safety performance tests, to verify the improvement effect of the composite coating on battery performance.
[0034] Embodiment 2
[0035] S1. Preparation of composite coating layer of positive electrode material:
[0036] (1) selecting 0.005 g of a suitable oxide solid electrolyte material and uniformly dispersing it in an organic solvent by a sol-gel method to form a stable oxide solution;
[0037] (2) selecting 0.005 g of a polymer solid electrolyte having high ionic conductivity and good flexibility, and dissolving it in 5 mL of an organic solvent having good compatibility to form a polymer solution;
[0038] (3) dispersing 1 g of the positive electrode active material in the mixture of the above oxide and polymer solution, and ensuring uniform coating by stirring, ultrasound or ball milling;
[0039] (4) vacuum drying the coated material at 80° C. or heat treating it in an inert atmosphere to remove excess solvent and form a dense oxide-polymer composite coating layer;
[0040] S2. Optimization of composite coating properties: By adjusting the ratio of oxide to polymer, the thickness of the coating, and the heat treatment conditions, the ion conductivity, mechanical strength, and electrochemical stability of the composite coating are optimized. The performance of the composite coating can also be further improved by adding a small amount of inorganic nanoparticles.
[0041] S3. Assembly of solid-state battery: using the modified positive electrode material, solid electrolyte, negative electrode material and separator, assembling into a battery according to conventional solid-state battery manufacturing process;
[0042] S4. Performance testing: Conduct electrochemical performance tests on the prepared solid-state batteries, including charge and discharge cycle stability, rate performance, energy density, coulombic efficiency, self-discharge rate and safety performance tests, to verify the improvement effect of the composite coating on battery performance.
[0043] Embodiment 3
[0044] S1. Preparation of composite coating layer of positive electrode material:
[0045] (1) selecting 0.02 g of a suitable oxide solid electrolyte material and uniformly dispersing it in an organic solvent by a sol-gel method to form a stable oxide solution;
[0046] (2) selecting 0.02 g of a polymer solid electrolyte having high ionic conductivity and good flexibility, and dissolving the same in 10 mL of an organic solvent having good compatibility to form a polymer solution;
[0047] (3) dispersing 1 g of the positive electrode active material in the mixture of the above oxide and polymer solution, and ensuring uniform coating by stirring, ultrasound or ball milling;
[0048] (4) vacuum drying the coated material at 150° C. or heat treating it in an inert atmosphere to remove excess solvent and form a dense oxide-polymer composite coating layer;
[0049] S2. Optimization of composite coating properties: By adjusting the ratio of oxide to polymer, the thickness of the coating, and the heat treatment conditions, the ion conductivity, mechanical strength, and electrochemical stability of the composite coating are optimized. The performance of the composite coating can also be further improved by adding a small amount of inorganic nanoparticles.
[0050] S3. Assembly of solid-state battery: using the modified positive electrode material, solid electrolyte, negative electrode material and separator, assembling into a battery according to conventional solid-state battery manufacturing process;
[0051] S4. Performance testing: Conduct electrochemical performance tests on the prepared solid-state batteries, including charge and discharge cycle stability, rate performance, energy density, coulombic efficiency, self-discharge rate and safety performance tests, to verify the improvement effect of the composite coating on battery performance.
[0052] In the present invention, the usage ratio of the oxide solid electrolyte, the polymer solid electrolyte, the organic solvent and the positive electrode active material is 0.005-0.02 g: 0.005-0.02 g: 5-10 mL: 1 g.
[0053] In the present invention, the oxide solid electrolyte includes at least one of aluminum oxide, zirconium oxide, and silicon oxide, and the polymer solid electrolyte includes at least one of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), and polyacrylonitrile (PAN).
[0054] In the present invention, the positive electrode active material is LiNiCoMnO 2 or LiNi o.8 Co o.1 Mo o.1 O 2 The organic solvent includes at least one of ethanol, acetonitrile, N-methylformamide, and tetrahydrofuran, and the thickness of the oxide and polymer solid electrolyte coating layer is 1 to 5 nm.
[0055] In the present invention, in S2, the inorganic nanoparticles are selected from titanium dioxide or carbon nanotubes.
[0056] In the present invention, in S3, the solid electrolyte is selected from one of a sulfide solid electrolyte, an oxide solid electrolyte or a polymer solid electrolyte, and the negative electrode material is selected from one of lithium metal, lithium alloy or silicon-based negative electrode.
[0057] A solid-state battery comprises a battery positive electrode material prepared by the above-mentioned preparation method, a solid electrolyte, a conductive agent and a binder.
[0058] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0059] Effect Example
[0060] The solid-state batteries provided by Examples 1-3 and Comparative Example (conventional solid-state batteries on the market) were subjected to the following performance tests for capacity testing and cycle testing, and the test results are shown in the following table:
[0061]
[0062] It can be seen from the above table that the oxide-polymer composite coating effectively reduces the interface resistance between the positive electrode and the solid electrolyte, promotes the rapid transmission of lithium ions, and improves the battery's charge and discharge efficiency and energy density. The flexibility of the polymer is combined with the high mechanical strength of the oxide to improve the structural stability of the battery during the charge and discharge process, and reduce the pulverization and peeling of the positive electrode material. By optimizing the composition and structure of the coating, the cycle life of the solid-state battery is significantly extended, the capacity attenuation is reduced, and the cycle stability and reliability of the battery are improved. The use of solid electrolytes fundamentally avoids the safety problems that may be caused by liquid electrolytes, such as leakage, combustion, explosion, etc. At the same time, the composite coating further enhances the thermal stability and chemical stability of the battery and improves the safety performance of the battery.
[0063] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0064] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a positive electrode material modified by a solid electrolyte composite coating, characterized in that: The specific steps include: S1. Preparation of composite coating layer of positive electrode material: (1) Selecting a suitable oxide solid electrolyte material and uniformly dispersing it in an organic solvent by a sol-gel method to form a stable oxide solution; (2) Selecting a polymer solid electrolyte with high ionic conductivity and good flexibility, and dissolving it in an organic solvent with good compatibility to form a polymer solution; (3) dispersing the positive electrode active material in the mixture of the above oxide and the polymer solution, and ensuring uniform coating by stirring, ultrasound or ball milling; (4) vacuum drying the coated material at 80-150° C. or heat treating it in an inert atmosphere to remove excess solvent and form a dense oxide-polymer composite coating layer; S2. Optimization of composite coating properties: By adjusting the ratio of oxide to polymer, the thickness of the coating, and the heat treatment conditions, the ion conductivity, mechanical strength, and electrochemical stability of the composite coating are optimized. The performance of the composite coating can also be further improved by adding a small amount of inorganic nanoparticles. S3. Assembly of solid-state battery: using the modified positive electrode material, solid electrolyte, negative electrode material and separator, assembling into a battery according to conventional solid-state battery manufacturing process; S4. Performance testing: Conduct electrochemical performance tests on the prepared solid-state batteries, including charge and discharge cycle stability, rate performance, energy density, coulombic efficiency, self-discharge rate and safety performance tests, to verify the improvement effect of the composite coating on battery performance.
2. The method for preparing a solid electrolyte composite coated modified positive electrode material according to claim 1, characterized in that: The usage ratio of the oxide solid electrolyte, the polymer solid electrolyte, the organic solvent and the positive electrode active material is 0.005-0.02g:0.005-0.02g:5-10mL:1g.
3. The method for preparing a positive electrode material modified by a solid electrolyte composite coating according to claim 1, characterized in that: The oxide solid electrolyte includes at least one of aluminum oxide, zirconium oxide, and silicon oxide, and the polymer solid electrolyte includes at least one of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), and polyacrylonitrile (PAN).
4. The method for preparing a positive electrode material modified by a solid electrolyte composite coating according to claim 1, characterized in that: The positive electrode active material is LiNiCoMnO2 or LiNi o.8 Co o.1 Mo o.1 O2, the organic solvent includes at least one of ethanol, acetonitrile, N-methylformamide, and tetrahydrofuran, and the thickness of the oxide and polymer solid electrolyte coating layer is 1 to 5 nm.
5. The method for preparing a positive electrode material modified by a solid electrolyte composite coating according to claim 1, characterized in that: In S2, the inorganic nanoparticles are selected from titanium dioxide or carbon nanotubes.
6. The method for preparing a positive electrode material modified by a solid electrolyte composite coating according to claim 1, characterized in that: In S3, the solid electrolyte is selected from one of a sulfide solid electrolyte, an oxide solid electrolyte or a polymer solid electrolyte, and the negative electrode material is selected from one of lithium metal, lithium alloy or a silicon-based negative electrode.
7. A solid-state battery, characterized in that: The invention comprises a battery positive electrode material prepared by the preparation method according to any one of claims 1 to 6, a solid electrolyte, a conductive agent and a binder.
Citation Information
Cited By
Composite positive electrode material of sulfide solid-state battery, preparation method of composite positive electrode material and secondary battery
CN120581578A